Initiatives of West African economic and monetary union (WAEMU) in regional integration - (:unkn) unknown (My University, 2022)
African States, like other parts of the world, have embarked on cooperation or regrouping strategies to face the multiple challenges of globalization. It is in this context that African countries have decided to unite within the framework of regional integration through the creation of the West African Economic and Monetary Union (WAEMU), created in 1994. However, all forms of regional integration throughout the world have not always had satisfactory results. This literature review therefore aims to analyze the main initiatives of WAEMU with a view to strengthen its regional integration. On the one hand, research shows that many initiatives have been undertaken in favor of integration. Several actions have been taken concerning macroeconomic policies such as the construction of common markets, the harmonization of legislation and the implementation of sectoral policies. But, on the other hand, the study reveals that despite all these initiatives, regional integration in the WAEMU space still remains a challenge because one cannot speak of true regional integration when intracommunity trade is still very low.
Keywords: African Research